Optimization of growth parameters for growth of high quality heteroepitaxial 3C-SiC films at 1200 degrees C - Wilhelm, Martin; Rieth, Marcel; Brandl, Marco; Wibowo, Rachmat Adhi; Hock, Rainer; Wellmann, Peter (Thin Solid Films, 2015)
In order to reduce the residual stress caused by the mismatch of thermal expansion coefficients of 3C-SiC layers grown on Si after cooling down to room temperature, the growth temperature was reduced from usually above 1300 degrees C to 1200 degrees C. Epitaxial layers with high crystalline quality were grown on 1 x 1 cm(2) (100) Si substrates. The layers were evaluated by means of x-ray diffraction (XRD), Raman measurements, scanning electron microscopy and atomic force microscopy. Full width at half maximum values of 0.19 degrees for XRD rocking curve measurements of the (200) 3C-SiC peak were achieved, indicating high crystalline quality of the layers and epitaxial growth. For optimized growth at 1200 degrees C a high C/Si-ratio, on-axis substrates and a layer thickness of over 1 mu m are necessary. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Cubic silicon carbide; Heteroepitaxy; X-ray diffraction; Raman spectroscopy